Potential of Easily Prepared Low-Cost Natural Clay for the Cationic Adsorption of Methylene Blue Dye - Susanti, Indri; Rosdiana, Silvi Rosiva; Sajidah, Happy Bunga Nasyirahul; Sholeha, Novia Amalia; Iqbal, Rendy Muhamad (Chemistry Department, The University of Brawijaya, 2024)
The research aims to synthesize and characterized the properties of Natural Clay as adsorbent of cationic methylene blue which was easly prepared low-cost to be natural clay powder. Prepared natural clay then characterized by XRD, FTIR, and XRF. The methylene blue adsorption was tested using batch method with further analysis by spectrophotometry UV-Vis. The adsorption data then be analyze kinetic perform. The result showed that methylene blue adsorption capacity of natural clay is up to 72.51% While the kinetic study of methylene blue adsorption using natural clay showed that methylene blue adsorption process was suitable with kinetic model of Pseudo Second Order.